Advanced Topics in Intelligent Information and Database Systems - Król, Dariusz; Nguyen, Ngoc Thanh; Shirai, Kiyoaki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents recent research in intelligent information and database systems. The carefully selected contributions were initially accepted for presentation as posters at the 9th Asian Conference on Intelligent Information and Database Systems (ACIIDS 2017) held from to 5 April 2017 in Kanazawa, Japan. While the contributions are of an advanced scientific level, several are accessible for non-expert readers. The book brings together 47 chapters divided into six main parts: • Part I. From Machine Learning to Data Mining. • Part II. Big Data and Collaborative Decision Support Systems, • Part III. Computer Vision Analysis, Detection, Tracking and Recognition, • Part IV. Data-Intensive Text Processing, • Part V. Innovations in Web and Internet Technologies, and • Part VI. New Methods and Applications in Information and Software Engineering. The book is an excellent resource for researchers and those working in algorithmics, artificial and computational intelligence, collaborative systems, decision management and support systems, natural language processing, image and text processing, Internet technologies, and information and software engineering, as well as for students interested in such research areas.
Part I: From Machine Learning to Data Mining -- Analyzing Accident Prone Regions by Clustering -- Analyzing Life Insurance Data with Diﬀerent Classiﬁcation Techniques for Customers' Behavior Analysis -- Classiﬁcation of Product Rating Using Data Mining Techniques -- MASS: a Semi-Supervised Multi-Label Classiﬁcation Algorithm with Speciﬁc Feature -- Parallel Self-organizing Map Using Shared Virtual Memory Buﬀers -- Parametric Optimization of the Selected Classiﬁers in Binary Classiﬁcation -- Prediction of Academic Performance During Adolescence Based on Socioeconomic, Psychological and Academic Factors -- A Super-Vector Deep Learning Coprocessor with High Performance-Power Ratio -- Part II: Big Data and Collaborative Decision Support Systems -- Bi-temporal Database Model for Legal Merger Transactions and Late-arriving Information Problem: the Case of Polish Merger Market -- Breathing Movement Analysis for Adjustment of Radiotherapy Planning -- Measuring Improvement in Access to Complete Data in Healthcare Collaborative Dabase Systems -- Rough Set Theory for Supporting Decision Making on Relevance in Browsing Multilingual Digital Resources -- The Social Inﬂuence on the Behavioral Intention to Use Mobile Electronic Medical Records -- Stock Prices Growth Pattern by the Emergency Demand After the Great East-Japan Earthquake -- Structure-Based Virtual Screening for Novel Modulators of Human Orexin 2 Receptor with Cloud Systems and Supercomputers -- Supply Chains of Cross-Border E-Commerce -- Towards Personalized Virtual Customer Experience -- Towards Big Management -- Part III: Computer Vision Analysis, Detection, Tracking and Recognition -- Combination of Collision Detection and Visibility Algorithms in Simulation of Eﬀective Placement of Anti-Air Elements -- A Combination of Deep Learning and Hand-Designed Feature for Plant Identiﬁcation based on Leaf and Flower Images -- An Eﬃcient Defect Classiﬁcation Algorithm for Ceramic Tiles -- Parking Assistant - Prediction of an Empty Parking Space inTime -- Recent Advances in the Field of Foreground Detection: An Overview -- Tracking of Bone Reparation Process with Using of Periosteal Callus Extraction based on Fuzzy C-Means Algorithm -- Part IV: Data-Intensive Text Processing -- Automatic Post-Editing of Kazakh Sentences Machine Translated from English -- Complex Technology of Machine Translation Resources Extension for the Kazakh Language -- Enhancing Latent Semantic Analysis by Embedding Tagging Algorithm in Retrieving Malay Text Documents -- Exploiting Distance Graph and Hidden Topic Models for Multi-label Text Classiﬁcation -- Financial Reports and Financial News - An Information Content Gap Analysis -- The Great National Photocorpus of 20th-Century Vietnamese. Origins, assumptions and goals -- The Impact of User Sentiment Aroused by The-day-of-the-week on the Recommendation Eﬀectiveness in Microblog -- Multi-Sentence Compression Using Word Graph and Integer Linear Programming -- A Performance Comparison of Feature Extraction Methods forSentiment Analysis -- A Study of Plagiarism Checker System Based on Chinese Word Segmentation and SQL Intersection Operation Technique -- Text Summarization Based on Classiﬁcation Using ANFIS -- Part V: Innovations in Web and Internet Technologies -- Analysis of Indoor Positioning Based on BLE -- A Fusion Technique of Schema and Syntax Rules for Validating Open Data -- Job Description Language for a Browser-Based Computing Platform - A Preliminary Report -- Measuring the Eﬀectiveness of Knowledge Driven Web Applications -- Responsive Data Table Solution with New Scrolling Control Gesture for Better User Experience -- Part VI: New Methods and Applications in Software Engineering -- Adaptation of an ANN-Based Air Quality Forecasting Model to a New Application Area -- Checking Compliance of Program with SecureUML Model -- Generation of Test Data using Genetic Algorithm and Constraint Solver -- Investigating the Issues of using Agile Methods in Oﬀshore Software Development in Sri Lanka -- A Method forAutomated Test Cases Generation from UML Models with String ConstraintS -- Mobile Application for Calculation of Optimal Route Between Searched Points of Interest -- On Implementation of the Assumption Generation Method for Component-Based Software Veriﬁcation.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence